Mobbing and its eff ects on the health of a selected sample of nurses in the Czech Republic - Václavíková, Klára; Kozáková, Radka (Nursing in the 21st Century, 2022)
MOBBING AND ITS EFFECTS ON THE HEALTH OF A SELECTED SAMPLE OF NURSES IN THE CZECH REPUBLICIntroduction. Mobbing is a systemic problem that aff ects all work sectors, including the healthcare sector. Healthcare professionals are a group that is exposed to a high level of stress and thus, to the risk of negative situations in the workplace. The prevalence of  mobbing in nurses is high. Mobbed nurses more often suff er from stressful headaches, insomnia, anxiety and describe depressive symptoms.Aim. The aim of this study is to determine the rate of mobbing in a selected sample of nurses and to describe how nurses perceive their state of health. To determine whether there is a statistically signifi cant connection among the incidence of mobbing, perceived state of health, age of nurses and the length of their practice.Material and methods. A descriptive, cross-sectional study was performed. The standardized tools Negative Acts Questionnaire-Revised and General Health Questionnaire-28 were used. The research group consisted of nurses working in the acute care departments of selected medical facilities.Results. A total number of 715 nurses from all the regions of the Czech Republic participated in the study. The rate of nurses’experience with negative acts in the workplace is 79.3%. Mobbed nurses report health disorders more often, especially in the area of somatic symptoms, anxiety, and insomnia. A higher number of negative acts are reported by younger nurses with a shorter period of overall nursing practice.Conclusions. The occurrence of mobbing in the selected sample of nurses in the Czech Republic was confi rmed. Mobbed nursesperceive and report deteriorating of their health condition.